PERANCANGAN DAN IMPLEMENTASI DATA WAREHOUSE PADA BADAN PUSAT STATISTIK KOTA SALATIGA - , Kristien Margi Suryaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The rapid advances in the sector of information technology has discovered a new era, the era of information which can be expected for accessing and achieving an accurate, fast and precise information. Including the sector of population data analyzing on The Central Bureau of Statistics on Salatiga, which aims to analyze population data, for example